2017
DOI: 10.12973/ejmste/79975
|View full text |Cite
|
Sign up to set email alerts
|

New Technologies Challenging the Practice of Journalism and The Impact of Education: Case of Northern Cyprus

Abstract: The development of online journalism has generated a convergent media environment. This study is based on the assumption that the development of this new form of journalism plays a pivotal role in the transformation of the dynamics of professional practices, news production process as well as audience use and participation. It concentrates on investigating how and the extent to which this role is observed and can be explained in the context of Northern Cyprus. In this regard, it is argued that the prevalent jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The role of DMTs in the 21st century can never be over-emphasized. Previous studies by Çatal (2017), andZelizer (2019), have demonstrated that the technology employed to facilitate the work of a journalist in electronic media has increased considerably over the past decade, especially in developed economies. In the developing world, however, a study by (Mare 2013) has suggested that a good number of journalists still apply traditional analog techniques in reporting news.…”
Section: Discussionmentioning
confidence: 99%
“…The role of DMTs in the 21st century can never be over-emphasized. Previous studies by Çatal (2017), andZelizer (2019), have demonstrated that the technology employed to facilitate the work of a journalist in electronic media has increased considerably over the past decade, especially in developed economies. In the developing world, however, a study by (Mare 2013) has suggested that a good number of journalists still apply traditional analog techniques in reporting news.…”
Section: Discussionmentioning
confidence: 99%
“…Third, we find studies examining the ethics and normative boundaries of the production of news stories using these new journalistic formats, including, for example, Sánchez-Laws and Utne (2019) and Aitamurto (2019); however, additional studies are needed to consolidate a standardized ethics and homogeneous regulations that can address the reality of these new ways of doing journalism. In its turn, a standardized ethics will require researchers that can contribute to studies on the teaching of new media and technological literacy skills and their application in the curricula of schools of journalism, especially in the light of their current scarcity (Çatal, 2017; Mabrook and Singer, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Seen in this light, academics around the world have studied the phenomenon of journalistic innovation from a range of different perspectives. Some have done so by proposing a categorization of new ways of telling the news, placing the focus on the audiovisual as opposed to the textual (Trillo-Domínguez and Alberich-Pascual, 2017), while others have studied it in terms of interactivity (Barredo-Ibáñez and Díaz-Cerveró, 2017), and even, newly emerging journalistic skills (Çatal, 2017;Ramírez et al, 2016). Of course, this list does not exhaust all possibilities.…”
Section: Theoretical Frameworkmentioning
confidence: 99%